Using a Distributional Semantic Model for Collocation Identification - Mosinyan, Anna; Petrasova, Svitlana (My University, 2020)
This paper proposes the approach to automatic collocation identification using both the distributional semantic model and POS-tagging. The authors suggest calculating PMI to obtain a sequence of collocations from the designed corpus of research abstracts. Then POS-tagging is applied to classify collocations extracted from the text corpus.
Keywords: distributional semantics; POS-tagging; collocation; text corpus; research abstracts